A Rare Case of Pseudomyxoma Peritonei: Where did its Culprit Originate? - Varshney, Saumya; Borkar, Ankita; Nagarsenkar, Ajit; Amonkar, Siddhi; Naik, Ankita (Archives of Clinical and Medical Case Reports, 2024)
Pseudomyxoma peritonei refers to accumulation of mucin in the peritoneal cavity leading to a gelatinous form of ascites. With its incidence ranging between 1-4 out of a million per year, it is an extremely rare entity to be encountered by surgeons and gynaecologists. We report a case of a 55-year-old patient who presented with complaints of abdominal distension and dull abdominal pain for 2 months. On examination, abdomen appeared grossly distended, a soft cystic mass was felt arising from pelvis and extending up to the epigastrium. Patient underwent an exploratory laparotomy followed by total abdominal hysterectomy with left salpingo ovariotomy and right salpingoopherectomy with infracolic omentectomy. Intra operatively, it was observed that entire intra-peritoneal cavity was filled with mucin, a large multiloculated cyst engulfing the left ovary was noted, on further examination of the bowel a thickened appendix with mucinous deposit over it was identified for which appendectomy was performed. On histopathology, pseudomyxoma peritonei was confirmed with mucinous carcinoma of appendix and mucinous cystadenocarcinoma of left ovary. Furthermore, on immunohistochemistry testing it was revealed two independent primary malignancies of left ovary and appendix were coexisting.